2008
DOI: 10.1016/j.jvs.2008.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Metalloproteinase expression in venous aneurysms

Abstract: The structural changes in the venous wall in addition to the increased expression of MMP-2, MMP-9 and MMP-13 in VA compared to NSV and VV suggests a possible causal role for these MMPs in their pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 25 publications
4
39
1
2
Order By: Relevance
“…cough) weakness of venous wall [6][7][8][9] . Although some authors reported no evident pathologic changes 10 reports of others included a detailed microscopic description of the lesions called endophlebohypertrophy and endophlebosclerosis 8,9,[11][12][13] , which was also found in the our case 1. Some histologic features of these findings were described also in clearly congenital jugular venous aneurysm; it had been present at birth 14 .…”
Section: Literature Review and Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…cough) weakness of venous wall [6][7][8][9] . Although some authors reported no evident pathologic changes 10 reports of others included a detailed microscopic description of the lesions called endophlebohypertrophy and endophlebosclerosis 8,9,[11][12][13] , which was also found in the our case 1. Some histologic features of these findings were described also in clearly congenital jugular venous aneurysm; it had been present at birth 14 .…”
Section: Literature Review and Discussionsupporting
confidence: 56%
“…Therefore it seems that venous aneurysms may also arise in congenitally predisposed persons as a consequence of aquired mechanisms 8 . At the molecular level, increased expression of some matrix metalloproteinases in the wall of venous aneurysms suggests a possible causal role in their pathogenesis 13 . Venous aneurysms occur equally between the sexes 5,8 or with a slight female predominance 15 .…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Venous aneurysms of vessels not associated with chronic venous hypertension (primary or congenital) demonstrate thinning of the medial layer of the venous wall. 12 The etiology of venous aneurysmal dilatation secondary to chronic venous disease is the same as for varicosed segments; persistent venous hypertension and abnormal valve function. One theory portends a turbulent flow pat- tern associated with a dysfunctional valve.…”
Section: Discussionmentioning
confidence: 99%
“…Venous aneurysms are divided into two as primary and secondary aneurysms [1]. Secondary ones are mainly due to trauma, infection, inflammation, venous valve insufficiency and arteriovenous malformations.…”
Section: Introductionmentioning
confidence: 99%
“…A clear aetiology has not been yet established. Recent literature states that structural changes take place in the vessel wall due to increased matrix metalloproteinases [1]. The most common location for a venous aneurysm is lower extremities with popliteal vein is the leading one.…”
Section: Introductionmentioning
confidence: 99%